2015
DOI: 10.18049/jcmad/329
|View full text |Cite
|
Sign up to set email alerts
|

A Drug Utilization Study in Glaucoma Patients in a Tertiary Care Hospital of Central India

Abstract: Glaucoma is considered as a chronic progressive and usually symptomatic disease that destroys retinal cells and is one of the leading cause of preventable blindness worldwide, including India according to World Health Organization (WHO) studies. Although dawn of newer topical agents have modernized the management of glaucoma, the cost of these drugs pose a major hindrance to successful treatment since it limits entrée and amenability. AIMS AND OBJECTIVES:To analyze current prescribing trends in anti-glaucoma d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…The average number of drugs per encounter in our study was 1.7, which is within the range of WHO ideal values (1.6-1.8). Similarly, studies from Northwestern Ethiopia and India reported values within the acceptable range of 1.72 and 1.8, respectively (14,15). Several studies from different countries reported average number of drugs per encounter values higher than our results and WHO standards ranging from 2.2 to 5.85 (4,5,(16)(17)(18)(19)(20).…”
Section: In This Retrospective Analysis Of Patient Data From the Obesity Outpatient Clinic Of Istanbul Medeniyet University Goztepe Trainsupporting
confidence: 74%
“…The average number of drugs per encounter in our study was 1.7, which is within the range of WHO ideal values (1.6-1.8). Similarly, studies from Northwestern Ethiopia and India reported values within the acceptable range of 1.72 and 1.8, respectively (14,15). Several studies from different countries reported average number of drugs per encounter values higher than our results and WHO standards ranging from 2.2 to 5.85 (4,5,(16)(17)(18)(19)(20).…”
Section: In This Retrospective Analysis Of Patient Data From the Obesity Outpatient Clinic Of Istanbul Medeniyet University Goztepe Trainsupporting
confidence: 74%
“…7,8 It has been endorsed that average number of drugs per prescription should be ≤2. 9 It is advisable to keep the number of drug prescriptions as low as possible since higher figures lead to an increased risk of drug interactions and an increase in hospital cost due to errors of prescribing. 10 Timolol, the most widely prescribed anti-glaucoma drug and it was most commonly prescribed (58%) in present study as well.…”
Section: Brand 43% 57% Yes Nomentioning
confidence: 99%
“…Timolol, a beta-adrenergic antagonist was the most prescribed antiglaucoma monotherapy among the study populationsimilar to previous reports on antiglaucoma utilization patterns among POAG patients. 20,21 In this study the combination of latanoprost, timolol and acetazolamide treatment regimen appeared to be the most effective therapy among the participants. The majority of the participants with reduced IOP on medication alone were on this triple regimen.…”
Section: Discussionmentioning
confidence: 66%